Editorial - Revista Educação Especial - Geovana Mendonça Lunardi Mendes; Kamila Lockmann; Márcia Denise Pletsch; Carlo Schmidt; Eliana Pereira de Menezes; Clenio Perlin Berni (Universidade Federal de Santa Maria (UFSM), 2018)
Editorial - 2018